LIFE CYCLE EVALUATION IN THE NATIONAL PARK MURÃÅ‡ PLAIN (SLOVAKIA) - Tomaskinova, Judita; Dubiel, Jan (European Scientific Journal, ESJ, 2013)
The article presents the evaluation results of „life cycle“ of the National Park Muráň Plain (Slovakia) based on self-assessment of stakeholders by IPAM methodology (Integrative Protected Area Management). Based on this methodology, we identified areas of management that should be targeted for improvement also recommendations are proposed to streamline management. Based on the results of evaluations, we can state that Basic Planning Phase in life cycle of evaluated area is least effective developed. For improvement of other phases is first of all necessary to improve communication and to ensure transparency in the process of providing information. In terms of relevant documents, which will contribute to more effective integrated management of nature and landscape protection in the NP Muráň Plain, we suggest a high attention to the most expeditious approval of the proposed zoning of the national park.